2014
DOI: 10.1038/bjc.2014.446
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer relapse after chemoradiotherapy correlates with CD163+ macrophages in primary tumour and CD11b+ myeloid cells in recurrences

Abstract: Background:We investigated the prognostic role of tumour-associated macrophages (TAMs) in patients with head and neck squamous cell carcinoma (HNSCC) treated with definitive chemoradiotherapy (CRT).Methods:The expression of CD68+, CD163+ and CD11b+ cells was assessed using immunohistochemistry in n=106 pre-treatment tumour biopsy samples and was correlated with clinicopathological characteristics, including T-stage, N-stage, grading, tumour localisation, age and sex as well as local failure-free survival (LFFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 51 publications
5
72
0
2
Order By: Relevance
“…The prognostic importance of tumor infiltration with CD3 þ and CD8 þ cells has been demonstrated in breast, esophageal, lung, ovarian, colon, and anal cancers (31). In addition, Balermpas and colleagues (30) reported that the intratumoral localization of TILs (in close proximity of tumor cells, in the tumor stroma and in the periphery) influences their prognostic impact. Recent studies by Taube and colleagues (20) and Tumeh and colleagues (32) have also demonstrated that the location of T-cell infiltrate and PD-L1-expressing cells within a tumor specimen is of particular importance; detection of CD8 þ TILs and PD-L1-expressing cells at the invasive margin was associated with better response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic importance of tumor infiltration with CD3 þ and CD8 þ cells has been demonstrated in breast, esophageal, lung, ovarian, colon, and anal cancers (31). In addition, Balermpas and colleagues (30) reported that the intratumoral localization of TILs (in close proximity of tumor cells, in the tumor stroma and in the periphery) influences their prognostic impact. Recent studies by Taube and colleagues (20) and Tumeh and colleagues (32) have also demonstrated that the location of T-cell infiltrate and PD-L1-expressing cells within a tumor specimen is of particular importance; detection of CD8 þ TILs and PD-L1-expressing cells at the invasive margin was associated with better response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, Balermpas and colleagues reported that the intratumoral localization of TILs influences their prognostic impact. 25 Tumeh et al suggest that the presence of TILs is not a dichotomous variable and that the density and location of TILs and their interaction with the PD-L1-positive tumor microenvironment should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages contribute to immune response against malignant cells by activating Th1 cells, whereas M2 macrophages produce an anti-inflammatory response via cytokine release that promotes tumor growth (52). In HNSCC, TAMs are associated with worse outcome postsurgery and chemoradiotherapy (53,54). Finally, Tregs, often expressed in patients with HNSCC, can suppress immune responses via production of IL-10 and TGF-β, using up environmental T-cell survival factors, and dysregulating local T cells (55).…”
Section: Immune System and Cancer Developmentmentioning
confidence: 99%